Analisis Strategi Guru dalam Mengembangkan Keterampilan Sosial Anak Autistic Spectrum Disorder (ASD) Usia 5-6 Tahun TK Pembina 1 Medan - Margareth Theresia Perangin-angin; Suri Handayani Damanik (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
This study aims to identify the teaching approach and methods used by teachers at TK Pembina 1 Medan in developing the social skills of children with Autistic Spectrum Disorder (ASD), specifically in the B Inovatif class. This research employed a qualitative approach with data collection techniques including interviews, observations, and documentation. The subjects of the study consisted of two teachers and one child with ASD, identified as Z. The results show that the teacher applies a student-centered learning approach, allowing children the freedom to choose activities that align with their interests and comfort. This approach is intended to facilitate the social development of the child by providing a more enjoyable and meaningful learning experience. Additionally, six teaching methods were employed, namely role-playing, cooperative learning, singing with movement, social activities based on real-life experiences, the use of media such as videos, and storytelling. Although some methods, such as role-playing, are still difficult for children with ASD to follow, the teacher adapts these methods to suit the child's needs and abilities. This study reveals that structured and flexible teaching approaches and methods are crucial in helping children with ASD gradually develop their social skills.